The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/bcr3640
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived xenografts of triple-negative breast cancer reproduce molecular features of patient tumors and respond to mTOR inhibition

Abstract: IntroductionTriple-negative breast cancer (TNBC) is aggressive and lacks targeted therapies. Phosphatidylinositide 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) pathways are frequently activated in TNBC patient tumors at the genome, gene expression and protein levels, and mTOR inhibitors have been shown to inhibit growth in TNBC cell lines. We describe a panel of patient-derived xenografts representing multiple TNBC subtypes and use them to test preclinical drug efficacy of two mTOR inhibitors, sirolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 75 publications
(113 reference statements)
3
43
0
Order By: Relevance
“…PDX are today, with genetically engineered cancer mouse models, a more relevant model because they are based on the graft of fresh primary tumor fragments directly from the patient to immunodeficient mice. PDX maintain the genetic and histologic features of the original tumor (18,26,27). For instance, a good prediction of patient treatment efficacy using PDXs has been reported (28).…”
Section: Discussionmentioning
confidence: 99%
“…PDX are today, with genetically engineered cancer mouse models, a more relevant model because they are based on the graft of fresh primary tumor fragments directly from the patient to immunodeficient mice. PDX maintain the genetic and histologic features of the original tumor (18,26,27). For instance, a good prediction of patient treatment efficacy using PDXs has been reported (28).…”
Section: Discussionmentioning
confidence: 99%
“…Given the up-regulation of the mTOR pathway in many chemoresistant cancer [2] , mTOR inhibitors provide a logical solution to re-sensitize tumor cells to chemotherapy or to delay the development of resistance to treatment. Recent studies have demonstrated the effectiveness of sirolimus (rapamycin) in solid tumors, such as metastatic breast [3] , pancreatic [4] , and renal carcinomas [5] . Sirolimus is a first generation mTOR inhibitor [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…5,17,18 Due to dependence on EGFR signaling, many TNBCs also require the mammalian target of rapamycin (mTOR) to mediate proliferation. 17,19 This observation has maintained interest in cytostatic molecules called rapalogues. Like other drugs, rapalogues accumulate in normal tissue, which cause dose-limiting side effects.…”
Section: Introductionmentioning
confidence: 99%